Receiving Planting Material of Mountain Savory (Satureja montana L.) at a Vegetative Reproduction - Jelezniak, Tamara; Zinaida, Vorniku (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Are shown data about a vegetative reproduction of mountain savory (Satureja montana L.). This method will allow receiving the saplings possessing all qualitative signs of a maternal plant. The next ways of receiving planting material were studied: by rooting of green cuttings and lignified 2–3-year and 4–5 summer cuttings. Green cuttings 7–8 cm long landed in the greenhouse on a depth of 4–5 cm to expressly paved way and took roots with the keeping of express heating environments and at the increased humidity. Lignified cuttings were shortened to 15–18 cm of length and planted on a depth of 10–12 cm on the open site with a possibility of watering. During vegetation in all options, an apical part of plants for the best development of side escapes and accumulation of root weight was removed, watering and loosening of row spacings were regularly carried out. The received planting material was qualitative with well-developed root system, with a diameter of 8–11 cm and length of the main root of 15–22 cm. The thickness of a root neck depending on a way of receiving saplings made 5–22 cm, the number of skeletal escapes of 5–15 units. Saplings from lignified cuttings were considerably more developed, than from green. So, the mass of 10 plants averaged 230 g and 250 g against 70 g, and the mass of a root part of 10 plants of 134 g and 313 g of 41 g. Green cuttings have a good root developing ability, but strongly suffer from drying and are subject to rotting, therefore, their rooting and further body height requires the creation of special conditions. Lignified cuttings have the greatest reserve of nutrients, therefore, the root forming at them proceeds more successfully at preventing from drying of the high layer of the soil. The rooting of green cuttings made 49%, lignified cuttings of 83–89%, at the same time from them 80–85% corresponded to the first category on biomorphological features.